Empowerment of smallholder female livestock farmers and its potential impacts to their resilience to agricultural drought - Lindie V. Maltitz; Yonas T. Bahta (AIMS Agriculture and Food, 2021)
Studies have determined the factors influencing agricultural drought resilience of smallholder farmers and implications for empowerment. Other than the Abbreviated Women's Empowerment in Agriculture Index (A-WEAI), studies do not provide an analysis of cultural or traditional beliefs and reflective dialogues on challenges of smallholder female livestock farmers. This study uses a mixed approach that includes a survey, A-WEAI, Pearson's chi-square coefficient, and reflective dialogue to analyze these challenges. The ability to adapt to agricultural drought is influenced by factors such as access to information, credit, productive resources, and available time, all of which are different for men and women. Our study found that 61.3% and 16.4% of the female and male farmers were disempowered. Domains that contributed the most to the disempowerment of the women and men were respectively time/workload (52.97% and 31.89%), access to and decisions on credit (17.7% and 21.4%), ownership of assets (11.3% and 8.5%), input into productive decisions (10% and 9.1%) and group membership (8% and 19.13%). No significant correlation for age, marital status, or level of education versus empowerment status of women was found. A significant correlation was observed between farming experience and the empowerment status of women. Reflective dialogue during interviews revealed that women struggled with access to finance, grazing, water, stock theft, lack of training and knowledge, and intimidation by male neighbors. Such findings help inform agricultural development strategies to develop or modify existing policies to enhance the resilience of farmers to agricultural drought and empowerment. Gender-specific agricultural projects should be encouraged to empower female farmers to improve their resilience to agricultural drought. The government should assist female livestock farmers in accessing credit and developing clear policies on land tenure issues. Mentorship programs should be encouraged to educate and support female smallholder farmers to enhance their agricultural drought resilience and empowerment.